2014
DOI: 10.3390/su6118310
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking Sustainable Development: Considering How Different Worldviews Envision “Development” and “Quality of Life”

Abstract: Abstract:The concept of sustainable development does not articulate what needs to be sustained, developed, or how, and is consequently intersubjective and intercultural. I therefore argue that it is essential to consider different worldviews when discussing sustainable development, and I offer broad, provisional suggestions as to how we can begin doing this. I first discuss how the notion of sustainable development at its heart is an attempt to unite conservation with growth. I then consider how different worl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 38 publications
0
31
0
Order By: Relevance
“…Economic shocks and ecological decline in the 1970s and early 1980s had clearly exposed the limits of economic growth -and welfare -in alleviating poverty and disparities (WCED, 1987;Harding, 2012). It is widely acknowledged that the original conceptualisation of sustainable development was vague -with dissent about this being necessary, supportive, or counterproductive (see Hedlund-de Witt, 2014). But the point of interest here is a considerable consensus among sustainability scholars on the original conceptualisation's transformative potential (Dedeurwaerdere, 2014 ).…”
Section: The Epistemological Roots Of Conflicting Development Paradigmsmentioning
confidence: 99%
See 2 more Smart Citations
“…Economic shocks and ecological decline in the 1970s and early 1980s had clearly exposed the limits of economic growth -and welfare -in alleviating poverty and disparities (WCED, 1987;Harding, 2012). It is widely acknowledged that the original conceptualisation of sustainable development was vague -with dissent about this being necessary, supportive, or counterproductive (see Hedlund-de Witt, 2014). But the point of interest here is a considerable consensus among sustainability scholars on the original conceptualisation's transformative potential (Dedeurwaerdere, 2014 ).…”
Section: The Epistemological Roots Of Conflicting Development Paradigmsmentioning
confidence: 99%
“…Authors like Hedlund-de Witt (2014) and Tàbara and Chabay (2013) elucidate how different worldviews shape our understanding of the concept of sustainable development. They also further underline the need for clarification of our epistemological background and for more reflexive and inclusive forms of policymaking.…”
Section: The Epistemological Roots Of Conflicting Development Paradigmsmentioning
confidence: 99%
See 1 more Smart Citation
“…This section, which discusses the Integrative Worldview Framework (IWF) in a general fashion, has been published in a slightly different version before (Hedlund‐de Witt ).…”
mentioning
confidence: 99%
“…This attention to values is certainly something to be admired; the importance of constructing narratives about environmental change that align with people's existing values and worldviews-which are diverse even within one country-is increasingly recognized (e.g. Crompton, 2010;Schwartz, 2012;Hedlund-de Witt, 2014). It has also been shown that catastrophic imagery regarding climate change is more likely to disempoewer and disengage publics than imagery that is more associated with solutions, and that this has important implications for imagining climate futures (O'Neill and Smith, 2013).…”
Section: Appealing To Valuesmentioning
confidence: 99%